Controlled Encapsulation of Functional Organic Molecules within Metal–Organic Frameworks: In Situ Crystalline Structure Transformation. Issue 12 (23rd January 2017) - Guan, Jinju; Hu, Yu; Wang, Yu; Li, Hongfeng; Xu, Zhiling; Zhang, Tao; Wu, Peng; Zhang, Suoying; Xiao, Gengwu; Ji, Wenlan; Li, Linjie; Zhang, Meixuan; et al.
Abstract : Functional organic molecules/metal–organic frameworks composites can be obtained by in situ crystalline structure transformation from ZIF‐L to ZIF‐8‐L under double solvent conditions. Interestingly, the as‐prepared molecules/ZIF‐8‐L composites with the leaf‐like morphology exhibit good fluorescence properties and size selectivity in fluorescent quenchers due to the molecular sieving effect of the well‐defined microporous ZIF‐8‐L.